Longwood area, general view of a private residence at 19 Clochester Street, Brookline, Massachusetts, 2 of 2. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of a house in the Longwood area of Brookline, Massachusetts. One of several slides taken in this area.; Caption on image: Longwood area (2) Residence, 19 Clochester St. Walking Tour 1868-71.; Binder Number 4. Pocket Number: 7.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.